Development and acquisition of knowledge of youth parasport coaches - Lepage, P.; Bloom, G. A.; Falcão, W. R. (Adapted Physical Activity Quarterly, 2023)
The purpose of this study was to understand the learning experiences and acquisition of knowledge of youth parasport coaches. Five able-bodied male participants (M = 39 years old), who coached youth with a physical disability for an average of 7.4 years, participated in individual interviews. An inductive thematic analysis identified patterns within and across the data, allowing for description and interpretation of the meaning and importance of the themes. The results showed that coaches learned mostly from informal experiences, particularly through mentoring, trial and error, or use of technology. In addition, these learning opportunities were influenced by personal, environmental, and social factors. These findings can help to guide current and future generations of coaches of youth participants with a physical disability by highlighting available resources and addressing several barriers and facilitators to their learning.